Are Escherichia coli Pathotypes Still Relevant in the Era of Whole-Genome Sequencing? - Robins-Browne, Roy M.; Holt, Kathryn E.; Ingle, Danielle J.; Hocking, Dianna M.; Yang, Ji; Tauschek, Marija (Frontiers in Cellular and Infection Microbiology, 2016)
The empirical and pragmatic nature of diagnostic microbiology has given rise to several different schemes to subtype E.coli, including biotyping, serotyping, and pathotyping. These schemes have proved invaluable in identifying and tracking outbreaks, and for prognostication in individual cases of infection, but they are imprecise and potentially misleading due to the malleability and continuous evolution of E. coli. Whole genome sequencing can be used to accurately determine E. coli subtypes that are based on allelic variation or differences in gene content, such as serotyping and pathotyping. Whole genome sequencing also provides information about single nucleotide polymorphisms in the core genome of E. coli, which form the basis of sequence typing, and is more reliable than other systems for tracking the evolution and spread of individual strains. A typing scheme for E. coli based on genome sequences that includes elements of both the core and accessory genomes, should reduce typing anomalies and promote understanding of how different varieties of E. coli spread and cause disease. Such a scheme could also define pathotypes more precisely than current methods.